2013
DOI: 10.1192/bjp.bp.112.118307
|View full text |Cite
|
Sign up to set email alerts
|

Late-life depression and risk of vascular dementia and Alzheimer's disease: systematic review and meta-analysis of community-based cohort studies

Abstract: Late-life depression is associated with an increased risk for all-cause dementia, vascular dementia and Alzheimer's disease. The present results suggest that it will be valuable to design clinical trials to investigate the effect of late-life depression prevention on risk of dementia, in particular vascular dementia and Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
703
3
36

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,046 publications
(797 citation statements)
references
References 36 publications
55
703
3
36
Order By: Relevance
“…Studies on NCDs have shown that many factors are associated with this disorder. These factors include a history of cardiovascular disease or hypertension, depression, and osteoporosis (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on NCDs have shown that many factors are associated with this disorder. These factors include a history of cardiovascular disease or hypertension, depression, and osteoporosis (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Prospective studies indicate that depression may also increase the risk of future dementia. 6,7 Still, the neurobiologic substrate of the relation between depression and AD remains poorly understood. Several studies have found structural brain abnormalities to be associated with late-life depression, including hippocampal volume reduction.…”
mentioning
confidence: 99%
“…There are also several sociodemographic and clinical factors such as age of onset and education levels which can limit the findings reported by the included trials. For instance, the presence of late-life depression symptoms 37 and low levels of education are significant predictors for development of dementia. 38,39 Several of the included studies lack information regarding MMSE and just one of the studies prospectively assures that the included patients did not develop any kind of dementia.…”
Section: ■ Discussionmentioning
confidence: 99%